Cryptotephra in SPC-14 ice core - Hartman, Laura; Helmick, Meredith; Kurbatov, Andrei V.; Yates, Martin (IEDA: US Antarctic Program Data Center, 2023)
This dataset includes cryptotephra data from the South Pole Ice Core (SPC-14).